The essential oils of the aerial parts of two Hypericum taxa (Hypericum triquetrifolium and Hypericum aviculariifolium subsp depilatum var. depilatum (Clusiaceae)) from Turkey - Yuce, Ebru; Bagci, Eyup (Taylor & Francis Ltd, 2012)
In this study, essential oil compositions of two Hypericum L. taxa (Hypericum triquetrifolium Turra. and Hypericum aviculariifolium Jaub. et Spach subsp. depilatum var. depilatum (Freyn et Bornm.) Robson) naturally grown in Turkey were determined using gas chromatography and gas chromatography-mass spectrometry systems. The essential oils were obtained by hydrodistillation from the aerial parts of plants. A total of 45 compounds were identified in the essential oils of H. triquetrifolium; 1-hexanal (18.8%), 3-methylnonane (12.5%) and alpha-pinene (12.3%). In this study, 41 components were identified in H. aviculariifolium subsp. depilatum var. depilatum oil; alpha-pinene (52.1%), germacrene D (8.5%) and beta-pinene (3.6%) were the predominant constituents. The essential oil analysis showed that monoterpene concentrations were higher than that of the sesquiterpenes in both oils. The results were discussed in the meaning of the usefulness of these plants and their chemicals as natural products and potential usage in chemotaxonomy.
Keywords: Hypericum; Clusiaceae; essential oil; alpha-pinene; 1-hexanal; chemotaxonomy